2018
DOI: 10.1186/s12967-018-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of chronic fatigue syndrome following burn injuries

Abstract: BackgroundThe overlapping symptoms and pathophysiological similarities between burn injury and chronic fatigue syndrome (CFS) are noteworthy. Thus, this study explores the possible association between burn injury and the subsequent risk of CFS.MethodWe used data from the Taiwan National Health Insurance system to address the research topic. The exposure cohort comprised of 17,204 patients with new diagnoses of burn injury. Each patient was frequency matched according to age, sex, index year, and comorbidities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Abnormal adrenocortical activity has been reported among CFS patients since 1981 [24]. We previously reported that burn injury can disturb HPA axis and increase risk of subsequent CFS [25]. The HPA axis provides the body with the capability to respond to stress, which is a self-regulated feedback system that maintains homeostasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal adrenocortical activity has been reported among CFS patients since 1981 [24]. We previously reported that burn injury can disturb HPA axis and increase risk of subsequent CFS [25]. The HPA axis provides the body with the capability to respond to stress, which is a self-regulated feedback system that maintains homeostasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…This NHI program was implemented in March 1995 and since then has gone on to represent nearly 99% of the 23.74 million Taiwan residents 25 . The details of the NHI program and LHID2000 can be found in previous studies 15 , 26 . Diagnoses were based on the International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM).…”
Section: Methodsmentioning
confidence: 99%
“…The multivariable models included adjusting for age, sex, and comorbidities of diabetes, obesity, renal disease, rheumatoid arthritis, HIV, malignancy, untreated hypothyroidism, sleep apnea, narcolepsy, HBV, HCV, depression, anxiety, bipolar affective disorders, schizophrenia, delusional disorders, dementia, anorexia and bulimia nervosa, and alcohol or other substance abuse. All analyses were performed using the SAS software version 9.4 (SAS Institute Inc., Cary, NC, USA) (URL: https://bityl.co/4Os8 ), and the significance level was set at 0.05 for the two-tailed tests 15 , 16 , 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Inhalation injury can upregulate several immune mediators such as interleukin (IL)-1RA, IL-6, IL-8, granulocyte colony-stimulating factor, and monocyte chemotactic protein 1 (Davis et al, 2013). Moreover, we have investigated the impact of the thermal injury on the risk of chronic fatigue syndrome (Tsai et al, 2018) through the numerous proinflammatory cytokines leading to the Systemic inflammatory response syndrome (SIRS) as the first phase of thermal injury (Nielson et al, 2017). Systemic inflammation in patients with a large burn area and inhalation injury may play a crucial role in the pathogenesis of AKI.…”
Section: Discussionmentioning
confidence: 99%